1988
DOI: 10.2166/wst.1988.0105
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Some Pathogenic and Facultative Pathogenic Bacteria in Groundwater

Abstract: In model experiments carried out in the laboratory the survival of bacteria in groundwater kept at 10±l °C was tested. Only two of the tested bacteria species did not survive longer than 10 - 30 days. Escherichia coli, Salmonella typhimurium, Pseudomonas aeruginosa and other pathogenic or facultative pathogenic bacteria survived up to 100 days or even more in ground-water with or without the addition of sand from an aquifer. These results can be of importance for determining groundwater protection zones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…It is possible that pathogens that are present at low levels in this water multiply when they are exposed to favorable environmental conditions or available nutrients. In fact, it has been shown that the levels of members of several genera of pathogenic bacteria decrease only slightly during 100 days in groundwater alone (7), and several studies have shown that sediments serve as reservoirs for fecal pathogens (2,5).…”
mentioning
confidence: 99%
“…It is possible that pathogens that are present at low levels in this water multiply when they are exposed to favorable environmental conditions or available nutrients. In fact, it has been shown that the levels of members of several genera of pathogenic bacteria decrease only slightly during 100 days in groundwater alone (7), and several studies have shown that sediments serve as reservoirs for fecal pathogens (2,5).…”
mentioning
confidence: 99%
“…Both temperature and water content could influence E. coli die-off in deer pellets. The effect of temperature on bacterial survival is well studied, and it is known that E. coli die-off typically occurs faster at high temperatures (31,32,50,55,65,66). The effect of water content is less well understood, and as of now, there is no general agreement on its effect on microbial inactivation rates.…”
Section: Discussionmentioning
confidence: 99%
“…Shorter survival of enteric bacteria was reported in acid soils (28,29). An increase in temperature was shown to increase growth rates of E. coli in river water (30) but reduce survival duration (31,32).…”
mentioning
confidence: 99%
“…523 524 Survival of several pathogenic and indicator/facultative pathogenic bacteria in a 525 single ground water source from Germany was evaluated by Filip, et al (1988). The ground 526 water source was well-characterized in terms of ionic and other chemical constituents; 527 notably, pH was 7.3 and TDS were 486 mg/L as determined by evaporation.…”
Section: Studies On Viruses and Bacteria 293mentioning
confidence: 99%